Jogging at CHI - Mueller, Florian ‘Floyd’; Marshall, Joe; Khot, Rohit Ashok; Nylander, Stina; Tholander, Jakob (2016)
HCI is increasingly paying attention to sports, and more and more CHI attendees are aiming to maintain being physically active while attending CHI. In response, we offer a SIG on the topic of sports-HCI and conduct it in a sportive way: we will go out of the conference venue and jog around San Jose while discussing the role of HCI in relation to sports. The goal is to actively shape the future of the field of sports-HCI.